English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

7x2 + 49x + 42

2007-10-02 07:48:31 · 5 answers · asked by alton l 1 in Science & Mathematics Mathematics

5 answers

7(x^2 + 7x+ 6) = 7(x+6)(x+1)

2007-10-02 07:56:15 · answer #1 · answered by John V 6 · 0 0

7x^2+49x+42

First take out a common factor of 7, as all three numbers are divisible by 7:

7(x^2+7x+6)

Then find to numbers that muliply to give you 6 but add up to 7, which are 1 and 6. So, this expression simplified is:

7(x+1)(x+6)

2007-10-02 07:56:31 · answer #2 · answered by Drew C 1 · 0 0

7x^2 + 49x + 42
'7' is a factor so 'take it out'.
7(x^2 + 7x + 6)
Next to factor the terms inside the brackets. since 'x^2' has a coefficient of '1' then we need to find two number which when multiplied together give 6 and when added together give 7.
This is done by writing down all the factors of '6'
6 x 1 = 6
3 x 2 = 6
So the first product is the one to use because '6' plus '1' = '7'.
7(x + 1)(x + 6) - this is your term fully factored.

2007-10-02 07:56:24 · answer #3 · answered by lenpol7 7 · 0 0

7x^2 + 49x + 42 = 0

7x^2 + 7x + 42x + 42 = 0

7x(x+1) + 42(x+1) = 0

(x+1) (7x + 42) = 0

=> x = -1 or x = -42/7
=> x = -1 or x = -6

I hope it helps.

2007-10-02 08:04:35 · answer #4 · answered by Ehsan R 3 · 0 0

7(x^+7x+6)

2007-10-02 07:54:30 · answer #5 · answered by brittneyisacracker 1 · 0 0

fedest.com, questions and answers